Genome-Wide Identification, Expression Patterns, and Functional Analysis of UDP Glycosyltransferase Family in Peach (Prunus persica L. Batsch) - Wu, Boping; Gao, Liuxiao; Gao, Jie; Xu, Yaying; Liu, Hongru; Cao, Xiangmei; Zhang, Bo; Chen, Kunsong (Frontiers in Plant Science, 2017)
Peach (Prunus persica L. Batsch) is a commercial grown fruit trees, important because of its essential nutrients and flavor promoting secondary metabolites. The glycosylation processes mediated by UDP-glycosyltransferases (UGTs) play an important role in regulating secondary metabolites availability. Identification and characterization of peach UGTs is therefore a research priority. A total of 168 peach UGT genes that distributed unevenly across chromosomes were identified based on their conserved PSPG motifs. Phylogenetic analysis of these genes with plant UGTs clustered them into 16 groups (A–P). Comparison of the patterns of intron–extron and their positions within genes revealed one highly conserved intron insertion event in peach UGTs. Tissue specificity, temporal expression patterns in peach fruit during development and ripening, and in response to abiotic stress UV-B irradiation was investigated using RNA-seq strategy. The relationship between UGTs transcript levels and concentrations of glycosylated volatiles was examined to select candidates for functional analysis. Heterologous expressing these candidate genes in Escherichia coli identified UGTs that were involved in the in vitro volatile glycosylation. Our results provide an important source for the identification of functional UGT genes to potential manipulate secondary biosynthesis in peach.